Energy recovery from municipal solid waste using pyrolysis technology: A review on current status and developments. (July 2021) - Hasan, M.M.; Rasul, M.G.; Khan, M.M.K.; Ashwath, N.; Jahirul, M.I.
Abstract: The utilisation of renewable sources of energy has become an integral part of sustainable development. Municipal solid waste (MSW) has great potential to be used as a renewable source of energy if it can be combined with modern technologies such as pyrolysis. Pyrolysis technology is regarded as a revolutionary and easy energy production process for converting MSW into biofuel. Thus, the aim of this review is to present the state-of-the-art data on energy recovery from MSW. The review also includes information on its environmental impacts, challenges associated with the use of pyrolysis and a set of potential guidelines to overcome the challenges. The rotary pyrolysis technique is found to be the most used process for pyrolysis of MSW, as it provides ample heat transfer with comparatively low energy consumption. Temperature is the dominant parameter which is widely studied in MSW pyrolysis. Intermediate temperatures during pyrolysis normally provide maximum yields of bio-oil. Furthermore, the interactions of various parameters can affect the pyrolysis process. Pyrolysis facilities should be equipped with emission control systems to make the MSW pyrolysis operation environmentally friendly. Overall, pyrolysis of MSW yields around 43% bio-oil, 27% biochar and 25% syngas. It can be concluded that pyrolysis has the potential to be used as an effective and eco-friendly technology to generate biofuel and other value-added products from MSW. Graphical abstract: Image 1 Highlights: Brief overview of worldwide generation and current management practices of MSW. Summary on studies of different pyrolysis processes and reactors used in managing MSW. Discussion on the influences of different components of MSW and pyrolysis parameters on pyrolysis products. Each component and parameter presents different chemical properties. Environmental degradation associated with pyrolysis technology and possible remedies.